Combination of new multifunctional molecules for erythematotelangiectatic rosacea disorder - Chajra H; Nadim M; Auriol D; Schweikert K; Lefevre F (Dove Medical Press, 2015)
Hanane Chajra,1 Mahdi Nadim,2 Daniel Auriol,3 Kuno Schweikert,1 Fabrice Lefevre1 1Induchem AG, Volkestwil, Switzerland; 2CBM-CNRS, Orléans Cedex, 3Libragen SA, Toulouse, France Background: Rosacea, a common chronic skin disorder, is currently managed by patient education, pharmacological drugs, medical devices (laser and light therapies), and use of proper skin cares. Unfortunately, none of these actual treatments used alone or in combination is curative, and so we proposed a dermocosmetic active ingredient to mitigate some aspects of the rosacea and particularly for erythematotelangiectatic rosacea. Methods: Dermocosmetic active ingredient is composed of three glucosylated derivatives of natural plants hydroxybenzoic acid and hydroxycinnamic acids (rosmarinic acid, gallic acid, and caffeic acid). Anti-inflammatory, anti-angiogenesis, and anti-degranulation studies were done on cellular models (keratinocytes, mast cells, and endothelial cells). Efficiency of the active ingredient in comparison to placebo was assessed clinically on human volunteers having erythematotelangiectatic rosacea. The active and placebo were applied topically twice a day for 28 days. Biometrical analyses were done using a siascope tool. Results: We found that the active ingredient decreases inflammation (inhibition of interleukin-8 and tumor necrosis factor release), decreases degranulation of mast cells (inhibition of histamine release), and controls angiogenesis mechanism (inhibition of the production of vascular endothelial growth factor and neovessel formation) on cellular models. Study on human volunteers confirmed macroscopically the efficiency of this active ingredient, as we observed no neovessel formation and less visible vessels. Conclusion: Although rosacea is a skin condition disorder that is difficult to heal, the studies have shown that this active ingredient could be a dermocosmetic support, especially for erythematotelangiectatic rosacea armamentarium. The active ingredient was topically applied on the face for 28 days and improved erythematotelangiectatic rosacea symptoms either by decreasing them (vessels are less visible) or by limiting their development (any neovessels). The active ingredient decreases inflammation (inhibition of interleukin-8 and tumor necrosis factor release), decreases degranulation of mast cells (inhibition of histamine release), and limits the angiogenesis process (inhibition of vascular endothelial growth factor production and neovessel formation). Keywords: rosacea, erythema, gallic acid, rosmarinic acid, caffeic acid, glucosylation